Implementasi Tradisi Wirid Yasin (Yasinan) di Desa Kota Bangun Sebagai Kajian Living Al-Qur’an - Husna, Sayidatul Husna Panjaitan; Minan, Muhammad Aufal (LPPM Institut Al Azhar Menganti Gresik, 2023)
This study aims to find out what is the basis for Kota Bangun Village to carry out this routine activity. Can it be said as an effort to revive the Qur'an or not. The results of this journal are that the implementation of Yasin’s wirid activities which are carried out every Friday night in Kota Bangun village includes efforts to revive the Qur’an among the local communicaty. This is also called the study of living Al-Qur’an. This study uses a cumulative research method, which is a study that focuses on observations that produce data in the form of sentences and words and seeks to explain and interpret the objects of observation according to the data produced. Based on the results of the data, it was stated that the Yasin wirid activity was carried out to spread the religion of Islam, as a means of inviting residents to goodness, getting closer to Allah, and establishing friendship between residents of Kota Bangun Village. This activity was also carried out on the basis of several hadiths which predict the reading of Yasin's letter on Friday nights. Even though these hadiths are weak in quality, there is nothing wrong with being used as a basis for doing something good.